2011
DOI: 10.1097/sla.0b013e318214b55a
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Prophylactic Mastectomy in Swedish Women at High Risk of Breast Cancer

Abstract: Bilateral prophylactic mastectomy is safe and efficacious in reducing future breast cancer in asymptomatic women at high risk. Unanticipated reoperations are common. Given the small number of patients centralization seems justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 45 publications
2
34
1
1
Order By: Relevance
“…However, AdH, which is considered to be a premalignant lesion, was found in 10% of our patients. In a recent Swedish study of Arver et al (25), premalignant or malignant lesions were found in 10% of patients, which coincides with the results of our study; in addition, there were also 2% of invasive cancers in their series.…”
Section: Reconstruction N=27supporting
confidence: 92%
“…However, AdH, which is considered to be a premalignant lesion, was found in 10% of our patients. In a recent Swedish study of Arver et al (25), premalignant or malignant lesions were found in 10% of patients, which coincides with the results of our study; in addition, there were also 2% of invasive cancers in their series.…”
Section: Reconstruction N=27supporting
confidence: 92%
“…Surgical techniques and breast reconstruction have been described in detail previously and were not changed during the study period (3,4). In brief, a subcutaneous skin-sparing mastectomy with immediate implant-based breast reconstruction was performed, using expandable or permanent implants.…”
Section: Methodsmentioning
confidence: 99%
“…Women with a family history of breast cancer and/or identified BRCA mutations may opt for bilateral risk-reducing mastectomy (BRRM), whereas patients with a personal history of breast cancer may consider contralateral risk-reducing mastectomy (CRRM). RRM is irrevocable and includes issues of psychological distress, negative impact on body image, sexual functioning and potential surgical complications (3). The clinical course for patients undergoing contralateral RRM, evaluated in median 4 years later, showed that 60% required at least one reoperation (4).…”
Section: Introductionmentioning
confidence: 99%
“…But the majority of mutation carriers [22,23] and also patients with sporadic breast cancer decide for implant-based immediate reconstruction [24]. This is accompanied by a recent fast development of new materials and techniques to improve long-lasting esthetic results in implant-based and mesh-or acellular dermal matrix (ADM)-supported breast reconstruction.…”
Section: Best Choice For Bilateral Breast Reconstructionmentioning
confidence: 99%